The source of Proterozoic anorthosite and rapakivi granite magmatism: evidence from combined in situ Hf–O isotopes of zircon in the Ahvenisto complex, southeastern Finland - Aku Heinonen; Tom Andersen; O. Tapani Rämö; Martin Whitehouse (2016)
The isotope compositions of massif-type anorthosites in Proterozoic anorthosite–mangerite–charnockite–granite (AMCG) complexes are commonly dominated by crustal values. Olivine-bearing anorthositic rocks in several AMCG suites have, however, been shown to display juvenile character, suggesting that variably depleted mantle reservoirs were involved in their genesis. A coupled in situ zircon Hf–O isotope dataset from the 1.64 Ga Ahvenisto AMCG complex in the 1.54–1.65 Ga Fennoscandian rapakivi granite–massif-type anorthosite province reveals correlated juvenile isotope signals (δ 18 O zrn = 5.4–6.6‰; initial ϵ Hf = −1.1 to +3.4) in the most primitive gabbroic rock type of the suite suggesting a depleted mantle origin for the anorthositic rocks. This signal is not as prominent in the more evolved co-magmatic anorthositic rocks (δ 18 O zrn = 6.3–7.8‰; initial ϵ Hf = −0.8 to +2.0), most probably owing to contamination of the mantle-derived primary magma by crustal material. A rapakivi granite associated with the anorthositic rocks has different isotope composition (δ 18 O zrn = 7.4–8.6‰; initial ϵ Hf = −2.1 to +0.5) that points to a crustal source.